A prospective study on biochemical disturbances among cases of acute diarrhoea in children attending a tertiary care hospital of South India - Ankireddy, Korsipati; Ravi Kumar, Tenali (International Journal of Contemporary Pediatrics, 2018)
Background: Diarrhoea is one of the commonest clinical entities encountered regularly in clinical practice. In India, at least 1.5 million children die due to acute diarrhoea per year. Timely recognition, high index of suspicion and thorough understanding of various clinical signs in different types of dehydration is necessary in preventing the deaths. The present study focuses on the different types of biochemical alterations and electrolyte disturbances in cases of acute diarrhoea among children. Methods: A prospective study with ethical committee consent was done at a tertiary care hospital for two years in department of Paediatrics. All cases of acute diarrhoea attending with signs and symptoms of moderate and severe dehydration were included. Clinical history and necessary biochemical investigations including serum electrolytes were performed. The results and data were entered in an excel sheet and analysed. Results: 250 cases were enrolled in the study with males (57.6%) and females (42.4%). 1month to 5 years with 84 cases (33.6%) was the most common age group with mean age of 11.48± 2.4 years. History of passage of loose motions was with a frequency ranging from 6-12 /day with a mean frequency was 8.12/day. 80.8%cases had some kind of electrolyte abnormality with majority having isolated Hyponatremia and a combined Hyponatremia and Hypokalemia (33.6%) each. Conclusions: Diarrhoeal disorders can be easily prevented with proper hand hygiene practices, health awareness programmes, increased breast-feeding practices and proper disinfection of water. Hyponatremia, hypokalemia, combined Hyponatremia and hypokalemia are major electrolyte abnormalities in cases of diarrhoea.